CORRELATION BETWEEN INTERLEUKIN 13 SERUM LEVELS AND SCORAD INDEX IN PATIENTS WITH ATOPIC DERMATITIS - Indranila Kurniasari; R. Sri Djoko Susanto; Sugastiasri Sugastiasri (Media Medika Muda, 2017)
Background: Atopic dermatitis is one of the most common inflammatory skin disorders with increasing prevalence. AD is a multifactorial disease influenced by a complex relationship between genetic and environmental factors. Genetic predisposition for atopic diseases may cause an expansion of Th2 cells activities, and IL-13 is an important mediator in Th2 immunity response. IL-13 has a role in the abnormal immune response against pathogens and decreased skin barrier function, two major predisposing factors for AD. The purpose of this study is to prove that there is a correlation between IL-13 serum levels and AD disease severity measured by the SCORAD index. Method: This is a cross-sectional analytic observational study. Research subjects are 37 patients with atopic dermatitis and 16 healthy controls. Serum samples were processed and analyzed at the GAKI Laboratory of Dr. Kariadi General Hospital Semarang. Results: There is a significant difference of IL-13 serum levels between patients with atopic dermatitis and healthy control (p=0.0001), and between the study group with mild, moderate and severe atopic dermatitis (p=0.0001). Analysis found a significant and very strong positive correlation (p=0.0001; r=0.911) between IL-13 serum levels and SCORAD index. Conclusion: There is a significant positive correlation between IL-13 serum levels and atopic dermatitis disease severity, which means that IL-13 serum level will increase with increasing disease severity of atopic dermatitis. Keywords: Atopic Dermatitis, Interleukin 13, Severity, SCORAD